Recent progress and future perspectives of ionic liquid-based carbon dioxide capture and conversion - Anum Zafar; Karolina Matuszek; Douglas R. MacFarlane; Xinyi Zhang (Green Energy & Environment, 2025)
Carbon dioxide accounts for about 80 percent of greenhouse emissions and the increasing CO2 emission has been identified as a critical environmental issue. On the other hand, CO2 is a potentially renewable resource of a single carbon molecule, and new technologies to utilize CO2 in producing net-zero fuels and chemicals are of global interest. Great efforts have been made in the development of new materials and processes for CO2 capture and utilization (CCU). Among them, ionic liquids (ILs) have attracted much attention due to their unique characteristics such as high CO2 solubility, high ionic conductivity, negligible volatility, non-flammability, wide electrochemical window, and high thermal stability, as well as good solvation ability. This review summarizes the most recent efforts devoted to IL-based absorption, catalysts, and CO2 capture and utilization processes. We discuss the factors that affect the interaction between ILs and CO2, impacting on the viscosity and CO2 solubility and preview the coupling of CO2 capture with electrochemical conversion of CO2. Finally, we provide an overview on the advantages and disadvantages of the IL-based process for practical applications.